A simple approach for detecting HLA-A*02 alleles in archival formalin-fixed paraffin-embedded tissue samples and an application example for studying cancer immunoediting - Witt, Johannes; Haupt, Saskia; Ahadova, Aysel; Bohaumilitzky, Lena; Fuchs, Vera; Ballhausen, Alexej; Przybilla, Moritz Jakob; Jendrusch, Michael; Seppälä, Toni T.; Fürst, Daniel; Walle, Thomas; Busch, Elena; et al. (HLA, 2023)
The HLA system represents a central component of the antigen presentation machinery. As every patient possesses a defined set of HLA molecules, only certain antigens can be presented on the cell surface. Thus, studying HLA type-dependent antigen presentation can improve the understanding of variation in susceptibility to various diseases, including infectious diseases and cancer. In archival formalin-fixed paraffin-embedded (FFPE) tissue, the HLA type is difficult to analyze because of fragmentation of DNA, hindering the application of commonly used assays that rely on long DNA stretches. Addressing these difficulties, we present a refined approach for characterizing presence or absence of HLA-A*02, the most common HLA-A allele in the Caucasian population, in archival samples. ...
Online veröffentlicht: 17. Oktober 2022
Gesehen am 22.11.2023